Investigation of modified platelet-rich plasma (mPRP) in promoting the proliferation and differentiation of dental pulp stem cells from deciduous teeth - Wen,J. (2016)
Stem cells from human exfoliated deciduous teeth (SHEDs) have great potential to treat various dental-related diseases in regenerative medicine. They are usually maintained with 10% fetal bovine serum (FBS) in vitro. Modified platelet-rich plasma (mPRP) would be a safe alternative to 10% FBS during SHEDs culture. Therefore, our study aimed to compare the proliferation and differentiation of SHEDs cultured in mPRP and FBS medium to explore an optimal concentration of mPRP for SHEDs maintenance. Platelets were harvested by automatic blood cell analyzer and activated by repeated liquid nitrogen freezing and thawing. The platelet-related cytokines were examined and analyzed by ELISA. SHEDs were extracted and cultured with different concentrations of mPRP or 10% FBS medium. Alkaline phosphatase (ALP) activity was measured. Mineralization factors, RUNX2 and OCN, were measured by real-time PCR. SHEDs were characterized with mesenchymal stem cells (MSCs) markers including vimentin, CD44, and CD105. mPRP at different concentrations (2, 5, 10, and 20%) enhanced the growth of SHEDs. Moreover, mPRP significantly stimulated ALP activity and promoted expression of RUNX2 and OCN compared with 10% FBS. mPRP could efficiently facilitate proliferation and differentiation of SHEDs, and 2% mPRP would be an optimal substitute for 10% FBS during SHEDs expansion and differentiation in clinical scale manufacturing.